Under heavy pressure Intense monitoring and accumulation of sanctions for young welfare recipients in Germany - Joachim Wolff; Gerard J. van den Berg; Arne Uhlendorff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
With the introduction of a new welfare benefit system in 2005, Germany implemented quite strict benefit sanctions for welfare recipients aged younger than 25 years. For all types of non-compliance except for missing appointments, their basic cash benefit is withdrawn for three months. A second sanction of the same type within one year implies a complete benefit cut for three months. We analyze the impact of these sanctions on job search outcomes and on transitions out of the labor force. Our analysis is based on administrative data on a large inflow sample of young male jobseekers into welfare in West Germany. We estimate separate models for people living alone and people living with their family, as sanctioned welfare recipients living with other household members can partly rely on their support and might react less by increasing search intensity and lowering reservation wages. We estimate the parameters of multivariate duration models taking selection based on unobservables into account. Our results suggest that both the first and the second sanction increase the probability of finding a job, but that these jobs go along with lower earnings due to first but not the second sanction. Moreover, first sanctions significantly increase the transition rate out of the labor force of both groups of young men, while second sanctions amplify this effect only for young men living in single households.
Keywords: J64; C41; C21; 330